Basic measurements of radiation at station Petrolina (2006-12 et seq) - Goncalves, André R; Pereira, Enio Bueno (Instituto Nacional de Pesquisas Espaciais, São José dos Campos, 2025)
This is a compilation of all short-wave and long-wave radiation datasets from Petrolina that were and are published in the frame of BSRN. New data will be added regularly. The data are subject to the data release guidelines of BSRN (https://bsrn.awi.de/data/conditions-of-data-release/).